Toxicity of barakol: Hepatotoxicity and subacute toxicity - Pumpaisalchai W. (2014)
Barakol, an active principle of Cassia siamea (Caesalpiniaceae), exhibits an anxiolytic property. This study was undertaken to evaluate the acute hepatotoxicity and subacute toxicity of barakol in rats. The LD50 of barakol after oral administration was 2.33 g/kg. In an acute hepatotoxicity study, single-oral administration of various doses of barakol (60, 100 and 200 mg/kg) were given to rats and the animals were sacrified at 24 hours after the administration. Results from a liver biopsy revealed no sign of liver damage when compared to those from a paracetamol treated positive control group. In a subacute toxicity test, barakol at doses of 60, 120 and 240 mg/kg were orally administered daily for a period of four weeks. A half of 240 mg/kg group, called a recovery group, was maintained for 2 further weeks without barakol administration. No mortality was observed in the controlled and barakol-treated animals. Body weight gain of the barakol-treated group significantly decreased (p < 0.05). From histological examination, the barakoltreated group showed only fatty changes in the liver, but hepatocellular necrosis was not identified. Barakol did not interfere with the hematological examination values. From blood chemistry determination, bilirubin was increased (p < 0.05) in a dosedependent manner and the value return to normal values within two weeks. Barakol in doses of 60-240 mg/kg also decreased triglycerides and the effect persisted for at least two weeks in the recovery group. In conclusion, barakol may disrupt liver function, especially lipid metabolism and bilirubin, in dose-dependent manner. These effects were reversible. The data indicated that barakol may be clinically used in short-term treatment. In repeated administration, serum bilirubin should be carefully monitored. © ISHS 2005.